2015
DOI: 10.1007/s11011-015-9763-0
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine induces oxidative stress and decreases the viability of rat astrocytes: possible relevance for the pathophysiology of neurodegeneration in phenylketonuria

Abstract: The aim of this study was to investigate the effects of phenylalanine on oxidative stress and some metabolic parameters in astrocyte cultures from newborn Wistar rats. Astrocytes were cultured under four conditions: control (0.4 mM phenylalanine concentration in the Dulbecco's Modified Eagle Medium (DMEM) solution), Phe addition to achieve 0.5, 1.0 or 1.5 mM final phenylalanine concentrations. After 72 h the astrocytes were separated for the biochemical measurements. Overall measure of mitochondrial function b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 43 publications
1
17
0
3
Order By: Relevance
“…We noted that 11 genes had a decreased expression significantly correlated with high plasma concentrations of Phe after multiple testing correction. These data support results of previous studies highlighting disturbance in redox system with reduction of total antioxidant status or unbalance of prooxidant-antioxidant system in blood samples of PKU patients (Sitta et al 2009;Sanayama et al 2011;Preissler et al 2016;Tavana et al 2016). Several plasma amino acids and urinary organic acids seem to be correlated with antioxidant expression profile.…”
Section: Discussionsupporting
confidence: 91%
“…We noted that 11 genes had a decreased expression significantly correlated with high plasma concentrations of Phe after multiple testing correction. These data support results of previous studies highlighting disturbance in redox system with reduction of total antioxidant status or unbalance of prooxidant-antioxidant system in blood samples of PKU patients (Sitta et al 2009;Sanayama et al 2011;Preissler et al 2016;Tavana et al 2016). Several plasma amino acids and urinary organic acids seem to be correlated with antioxidant expression profile.…”
Section: Discussionsupporting
confidence: 91%
“…Although phenylalanine is crucial in the production of proteins or other molecules, the accumulation of phenylalanine can cause toxicity and damage to neuronal cells, which in turn disrupt the cognitive function [71]. High concentrations of phenylalanine in the cerebral cortex of mice have also been reported to induce the occurrence of oxidative stress and reduce the viability of astrocytes [72]. On the other hand, the glutathione metabolite pathway was found to be activated in the n-IF group.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Preissler et al [37] found that Phe increase oxidative stress and consequently cell death in astrocytes. They showed that pathological concentrations of Phe in PKU patients decrease astrocytes viability.…”
Section: Discussionmentioning
confidence: 99%